The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1210/jcem-71-4-963
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Hypogonadism in Older Men: Its Relation to Impotence*

Abstract: The relation of the reproductive endocrine system to impotence in older men was examined by measuring the concentrations of testosterone (T), bioavailable testosterone (BT), LH, and PRL and body mass index (BMI) in 57 young controls (YC), 50 healthy potent older controls attending a health fair (HF), and 267 impotent patients (SD). The SD and HF had markedly reduced mean T and BT values compared to YC. When adjusted for age and BMI there was no difference in BT between potent and impotent older men. The percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
1
7

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(117 citation statements)
references
References 34 publications
7
102
1
7
Order By: Relevance
“…Although some follow-up studies failed to detect age-related decline in plasma testosterone levels in older men [99][100][101][102][103][104], subsequent population-based cross-sectional and longitudinal studies have confirmed progressive loss of testosterone with aging in healthy men [96,[105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. Mirroring this decline in plasma testosterone concentration is an age associated increase in sex-hormonebinding globulin (SHBG) level [117], a major plasma carrier of testosterone, resulting in even more dramatic decreases in unbound free testosterone [110,[123][124][125], and weakly bound bioavailable testosterone [126,127]. [In healthy male adults, circulating testosterone exists in three forms: testosterone strongly bound to SHBG, testosterone weakly bound to albumin and free testosterone].…”
Section: Humansmentioning
confidence: 99%
“…Although some follow-up studies failed to detect age-related decline in plasma testosterone levels in older men [99][100][101][102][103][104], subsequent population-based cross-sectional and longitudinal studies have confirmed progressive loss of testosterone with aging in healthy men [96,[105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. Mirroring this decline in plasma testosterone concentration is an age associated increase in sex-hormonebinding globulin (SHBG) level [117], a major plasma carrier of testosterone, resulting in even more dramatic decreases in unbound free testosterone [110,[123][124][125], and weakly bound bioavailable testosterone [126,127]. [In healthy male adults, circulating testosterone exists in three forms: testosterone strongly bound to SHBG, testosterone weakly bound to albumin and free testosterone].…”
Section: Humansmentioning
confidence: 99%
“…Já a resposta ao Clomifeno é normal e o seu uso em baixas doses por longo prazo leva à normalização androgênica (5). O conjunto destes achados laboratoriais indica uma possível deficiência na liberação de LHRH (3-5), cuja causa poderia ser qualquer uma das que levam a uma redução dos níveis de testosterona, tais como stress (6,7), abuso de álcool (8), doenças sistêmicas crônicas ou agudas (9), idade avançada e outras (8,10,11).…”
Section: Discussionunclassified
“…There appear to be age related changes in the Leydig cells and elevated LH levels have been found in association with elevated FSH (Nieschlag et al, 1982;Gray et al, 1991) and reduced sperm production . Others have found unchanged LH levels (Zumoff et al, 1982;Korenman et al, 1990) or reduction in LH pulse amplitude (Veldhuis et al, 1992) consistent with hypogonadotropic hypogonadism. Further evidence for declining pituitary function is a reduced and delayed response to gonadotrophin releasing hormone (GnRH) .…”
Section: Ageingmentioning
confidence: 98%